Strategi Peningkatan Pertanian melalui Sosialisasi Pupuk Organik dan Budidaya Indigofera di Desa Sukawening, Kabupaten Bogor - Zaenal Abidin; Aushafa Dyazra; Zaki Maharani; Cika Hilda Fransiski; Dyo Dion Dewantara; Elsa Amelya Fitriany; Muhamad Luthfi Asyidiq; Muhamad Zidan Rahmat; Neng Rahayu Novita; Nur Hafifah; Nur Hanifah; Riska Nurul Putri; Sheila Gracia Ginting (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
Sustainable agriculture is the management of agricultural business resources to help changing human needs while maintaining or improving the quality of the environment and conserving natural resources. One example is